Effectiveness and reliability of air transport traffic control - Дем'янчук, B. C. (Proceedings of National Aviation University (archive), 1998)
Considered are general problems of complex systems effectiveness and problems concerning estimation of effectiveness of air transport traffic control systems taking into account their reliability